Towards an understanding of language learner self-concept - Mercer, Sarah. (Educational Linguistics, 2011)
This book contributes to our growing understanding of the nature and development of language learner self-concept. It assesses the relevant literature in the disciplines of psychology and applied linguistics and describes in-depth, qualitative research examining the self-concepts of tertiary-level EFL learners. Although researchers in applied linguistics and SLA have recognized the importance of self-constructs, there remains little empirical work in the context of foreign language learning that focuses exclusively and at length on this central psychological construct. The content of this monograph draws on interdisciplinary sources, with input from psychology and applied linguistics. It will appeal to students and researchers interested in language-learner psychology as well as self-related constructs in general. The text provides insights into how learners view themselves, and how these self-beliefs can develop and affect the progress of an individual’s language learning. List of appendices -- List of figures -- Glossary -- Chapter 1 introduction -- Chapter 2 what is self-concept? -- Chapter 3 understanding self-concept in the FLL context -- Chapter 4 how do learners form their self-concepts? -- Chapter 5 internal frames of reference in FL self-concept formation -- Chapter 6 external frames of reference in FL self-concept formation -- Chapter 7 implications for educators and researchers -- References -- Appendices.